2014
DOI: 10.1002/jor.22681
|View full text |Cite
|
Sign up to set email alerts
|

Temporary inductions of matrix metalloprotease-3 (MMP-3) expression and cell apoptosis are associated with tendon degeneration or rupture after corticosteroid injection

Abstract: Corticosteroid injections are widely used to treat enthesopathy and tendinitis, but are also associated with possible side effects, such as tendon degeneration or rupture. However, the mechanism of tendon degeneration or rupture after corticosteroid injection remains controversial. The purpose of this study was to reveal the mechanism of tendon degeneration or rupture after injection of triamcinolone acetonide (TA) or prednisolone (PSL). Forty-two rats were divided into 3 groups: A normal saline injection grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 44 publications
1
34
0
3
Order By: Relevance
“…One factor to consider regarding the dose of steroid would be patient habitus; therefore, the notion of ‘one dose fits all’ may be somewhat naïve and is potentially lacking in clinical reasoning. CSIs have also been associated with tendon degeneration and rupture54 so could dosage affect that risk? The use of LA was also variable with some not using LA, and those that did, using different volumes and types of anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…One factor to consider regarding the dose of steroid would be patient habitus; therefore, the notion of ‘one dose fits all’ may be somewhat naïve and is potentially lacking in clinical reasoning. CSIs have also been associated with tendon degeneration and rupture54 so could dosage affect that risk? The use of LA was also variable with some not using LA, and those that did, using different volumes and types of anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…16 In spite of many studies suggesting non inflammatory but degenerative nature of tennis elbow still many orthopedic surgeons often inject corticosteroids for tennis elbow. [7][8][9] Current literature suggests injection of corticosteroids gives only short term pain relief and in the midterm and long term follow up it has no role. 17 Biologically, corticosteroids do not address the underlying pathobiology of tendinopathy but rather have deleterious effect and may result in induction of cell apoptosis and breakdown of collagen and matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, corticosteroids do not address the underlying pathobiology of tendinopathy and may result in induction of cell apoptosis and breakdown of collagen and matrix. 9,10 Autologous blood injection delivers blood borne cellular and humoral mediators to stimulate the regeneration process within the tendon. 11 Therefore, the present study has been designed to investigate the outcome after injection of autologous blood and local anaesthetic mixture for tennis elbow after 1, 4, 8 and 12 weeks also at 6 and 9 months.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that MMP-1, 3, and 13 are closely related to OA occurrence and progression (Hossain et al, 2008;Aerts et al, 2014;Muto et al, 2014). Among them, MMP-3 could cleave multiple extracellular matrixes including gelatin and adhesion protein, and stimulate MMP-1 synergy.…”
Section: +mentioning
confidence: 99%